Attosecond physics phenomena at nanometric tips. (9th August 2018) - Krüger, Michael; Lemell, Christoph; Wachter, Georg; Burgdörfer, Joachim; Hommelhoff, Peter
Abstract: Attosecond science is based on electron dynamics driven by a strong optical electric field and has evolved beyond its original scope in gas-phase atomic and molecular physics to solid-state targets. In this review, we discuss a nanoscale attosecond physics laboratory that has enabled the first observations of strong-field-driven photoemission and recollision at a solid surface: laser-triggered metallic nanotips. In addition to the research questions of rather fundamental nature, femtosecond electron sources with outstanding beam qualities have resulted from this research, which has prompted follow-up application in the sensing of electric fields and lightwave electronics, ultrafast microscopy and diffraction, and fundamental matter-wave quantum optics. We review the theoretical and experimental concepts underlying near-field enhancement, photoemission regimes and electron acceleration mechanisms. Nanotips add new degrees of freedom to well known strong-field phenomena from atomic physics. For example, they enable the realization of a true sub-optical-cycle acceleration regime where recollision is suppressed. We also discuss the possibility of high-harmonic generation due to laser irradiation of metallic nanostructures.